GEOPHYSICAL AND GEOTECHNICAL STUDY FOR ASSESSING THE POTENTIAL OF LANDSLIDE DISASTERS: A CASE STUDY IN KRUENG SABET, ACEH JAYA, INDONESIA (GEOMATE Journal, 2025)
This study investigates landslide susceptibility in the Krueng Sabet Lamno region of Aceh Jaya by integrating geophysical and geotechnical methods, addressing a key gap where these approaches are often applied in isolation. The central hypothesis is that correlating resistivity, seismic refraction, and Cone Penetration Test (CPT) data can more accurately identify weak zones prone to slope failure than single-discipline analyses. Field investigations along the Jantho–Lamno road revealed Silty Sand and Fine Sand layers as potential slip-prone horizons, with CPT data highlighting low-resistance zones and high pore-water vulnerability. Seismic refraction delineated shallow layers, while resistivity models detected low-resistivity anomalies corresponding to water-saturated sediments. From these datasets, three principal subsurface layers were interpreted: Sand and Clay, Weathered Bedrock, and Limestone Boulder. It is emphasized that these interpretations represent subsurface models rather than direct geological confirmation from surface outcrops. Results demonstrate that Silty Sand layers, although overlain by seemingly stable Fine Sands, are critically susceptible under heavy rainfall, groundwater rise, or additional load. The novelty of this study lies in its integrated approach, providing a holistic characterization of slope instability that strengthens disaster mitigation strategies and offers a replicable methodological framework for other landslide-prone regions.